1980
DOI: 10.2136/sssaj1980.03615995004400030017x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Nitrogen‐15 and Total Nitrogen in Some Virgin and Cultivated Soils

Abstract: Soil cores were taken from six locations representing three virgin and three cultivated soils in increments of 15 or 30 cm down to depths ranging from 120 to 300 cm. The number of samples of an individual soil profile varied from 20 to 96, though smaller numbers of some subsurface horizons were obtained at two locations where very rocky conditions were encountered. Frequency distribution analysis of δ15N values and of total N showed that they were log‐normally distributed in about half the groups of samples. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…Soil N generally has positive values of d 15 N, but there can be exceptions, depending on the ecosystem type (Broadbent et al 1980;Shearer and Kohl 1986;Vitousek et al 1989). Soil 15 N enrichment is generally attributed to a very slight discrimination against 15 N during biological N 2 ®xation combined with a generally larger discrimination against 15 N in N 2 production during denitri®cation; the enzymatic fractionation factor b ranging from 1 to 1.002 for N 2 ®xation (Minagawa and Wada 1986;HoÈ gberg 1997) and from 1 to 1.033 for denitri®cation (Mariotti et al 1982;Yoshida et al 1989;HoÈ gberg 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Soil N generally has positive values of d 15 N, but there can be exceptions, depending on the ecosystem type (Broadbent et al 1980;Shearer and Kohl 1986;Vitousek et al 1989). Soil 15 N enrichment is generally attributed to a very slight discrimination against 15 N during biological N 2 ®xation combined with a generally larger discrimination against 15 N in N 2 production during denitri®cation; the enzymatic fractionation factor b ranging from 1 to 1.002 for N 2 ®xation (Minagawa and Wada 1986;HoÈ gberg 1997) and from 1 to 1.033 for denitri®cation (Mariotti et al 1982;Yoshida et al 1989;HoÈ gberg 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, plants taking nitrogen exclusively from the soil might frequently have an 15N abundance different than that of plants assimilating nitrogen from both soil and air (e.g. Broadbent et al 1980;Rennie et al 1976;Ledgard et al 1984;Shearer et al 1978;Shearer and Kohl 1989;Virginia et al 1988). …”
mentioning
confidence: 99%
“…Other studies have reported impossible %Ndfa values (Sanginga et al, 1990;Hansen and Vinther, 2001), and support the concern of Broadbent et al (1980) that excessive variation in d 15 N can limit the use of the natural abundance method to obtain quantitative estimates of N fixation. Guinto et al (2000) also was unable to estimate N fixation by Acacia sp.…”
Section: Suitability Of the 15 N Natural Abundance Methods At Bmefmentioning
confidence: 76%